Effect of dietary supplement (cevas) on the chemical composition of wild fish Brycon falcatus Müller & Troschel, 1844 in the Teles Pires river basin - Matos, Liliane Stedile; Silva, João Otávio dos Santos; Beckmann, Marcos Alencar; Moreira, Paula Sueli Andrade; Oliveira, André Soares de; Carvalho, Lucélia Nobre (Acta Scientiarum. Biological Sciences, 2017)
In the Teles Pires River watershed, one of the most common techniques currently used by fishermen to catch fish is to provide a food supplement commonly known as “cevas”. The purpose of this study was to compare the chemical composition of fillets from Brycon falcatus that were caught in both the presence and absence of cevas. The fish were sampled monthly and captured in the following conditions: the Tapaiúna River without cevas, the Teles Pires River with one ceva/100 m, the Celeste River with one ceva/500 m, the Verde River with one ceva/1000 m and the Cristalino River (control area). Subsequent to capture, the fish were euthanized and preserved on ice to determine their water, ash, crude protein and fat contents. Fillets of fish from the control area exhibited a lower level of crude protein (17.81%) compared with that of fish from the other rivers, which did not differ amongst one other. The fillets of fish from the river with the greatest density of cevas (1/100 m) exhibited a higher fat content (3.63%) than that of fish from the control area (1.51%). Thus, the cevas changed the chemical composition of B. falcatus fillets.